Topical map for continuing education: AHP expert survey - Thomas Neukirchen; Matthias Klumpp (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
This contribution presents an analysis of recent trend topics in logistics and supply chain management with a focus on education and training on the job, applying an Analytic Hierarchy Process (AHP).Based on a comprehensive literature survey for the identification of trends that have persisted over the ten years considered (2005-2015), expert interviews have been conducted, aggregated and evaluated with an AHP. The particular context for this contribution is the research project MARTINA, which is concerned with innovative design for logistics education and thus encompasses iterative development of education software (app for mobile training). With this in mind, a dichotomous structure according to professional areas has been chosen ('blue-collar' and 'white-collar') for the questionnaires and corresponding hierarchy.Our AHP had the goal of identifying topics for the design prototype (android-based app). Criteria included addressed the target groups 'blue collar' as well as 'white collar'; 14 alternatives were to be ranked and 45 completely answered questionnaires have been evaluated with the resultant ranking e-mobility, sharing economy, first aid training, cooperation, and diversity as the top 5 over both groups.The resultant topical ranking yields interesting results: First, we present an updated assessment of topics which will significantly shape logistics, logistics research and the related debate in the near future. Second, our results serve as guidelines for the development of new education concepts and are directly informing the design efforts taking place in the aforementioned project, thus being transformed into artifacts of the design cycle of an android-based smartphone and tablet application.
urn:nbn:de:gbv:830-88217803; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; Analytic Hierarchy Process; trend topics; education; training